2009
DOI: 10.1080/01443610903052073
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and significance of antiphospholipid antibodies in selected at-risk obstetrics cases: A comparative prospective study

Abstract: In a prospective comparative study we screened 112 women with a past history either of pre-eclampsia, eclampsia, recurrent abortion, IUGR, IUFD or abruptio placentae, with no apparent aetiology and a demographically matched cohort of 106 women having a past history of uncomplicated pregnancy outcome for the presence of antiphospholipid antibodies (aPL) and their significance. In the former group, the prevalence of aPL ranged from 10-46.87% compared with 8.49% in the later group. In women with the presence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
0
9
2
Order By: Relevance
“…In this study IgG and IgM antibodies were seen in 1 (1.3 %) and 3 (3.8 %) patients respectively. The prevalence is lower than that observed by other authors [15,16]. The prevalance of LA was thrice that of ACA and this observation was in contrast to other studies [6,30].…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…In this study IgG and IgM antibodies were seen in 1 (1.3 %) and 3 (3.8 %) patients respectively. The prevalence is lower than that observed by other authors [15,16]. The prevalance of LA was thrice that of ACA and this observation was in contrast to other studies [6,30].…”
Section: Discussioncontrasting
confidence: 56%
“…In a study on 30 Indian women with unexplained fetal loss, LA was observed in 16.6 % patients [17]. Saha et al [15] reported LA in 13.4 % patients with obstetric complications. Vora et al [16] observed LA positivity in 8.1 % of 430 women with fetal loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conceivably, an increased risk for hypertension in these patients may lead to a higher risk for pre-eclampsia, a wellrecognized pregnancy complication among patients with antiphospholipid syndrome (46). The main weakness of our paper is that of all meta-analyses: it is limited by the quality of the studies included.…”
Section: Discussionmentioning
confidence: 89%
“…Antiphospholipid antibodies have been reported as prevalent (10% to 30%) among women with preeclampsia. 27,28 Excluding aPTT from our de nition of the outcome "abnormal coagulation" was felt to be appropriate because clinicians clearly did not feel it was an important investigation.…”
Section: Discussionmentioning
confidence: 99%